Stare numery - Łopieńska, Barbara N. (1949-2004).; Szymańska, Ewa (dziennikarka). (Londyn : Aneks, 1986)
Dotyczy pisma "Po prostu".
Keywords: Po Prostu (czasopismo ; Polska ; 1947-1957 ; 1990-1991).; Prasa i polityka -- Polska -- 1945-1970.